Electrospun Composite Polymer Electrolyte Membrane Enabled with Silica‐Coated Silver Nanowires. Issue 45 (17th November 2021) - Gan, Huihui; Li, Shaoqiao; Zhang, Yong; Wang, Jirong; Xue, Zhigang
Abstract: Poly(ethylene oxide) (PEO)‐based polymer electrolyte has widely been considered as a promising material for high‐performance lithium metal batteries (LMBs) owing to the high safety, low cost, and excellent electrochemical stability. However, PEO‐based solid polymer electrolyte (SPE) has always been suffered with a poor mechanical strength and low room‐temperature ionic conductivity owing to its highly crystalline ethylene oxide (EO) chains. Especially, PEO‐based SPE exhibits an unstable framework at elevated temperature (exceed melting temperature), thus leading to the poor electrochemical performances. Here, the electrospun composite polymer membrane (CPM) based on poly(vinylidene fluoride‐hexafluoropropylene) (PVDF‐HFP) is fabricated by introduction of silica‐coated silver nanowires (AgNWs@SiO2 ). The PEO/LiTFSI is incorporated into the obtained PVDF‐HFP/AgNWs@SiO2 CPM to form the PEO‐based SPE. The composite polymer electrolyte membrane (CPEM) exhibits a high mechanical strength and wide electrochemical stability window (>5.0 V vs. Li + /Li) at 60 °C. The Li/CPEM/LiFePO4 cells also show a favorable cycle life at different rates and 92.7 mAh g −1 (2 C) of discharge specific capacity at 90 °C. Consequently, the PVDF‐HFP/AgNWs@SiO2 CPEM can exhibit an ideal application prospect for LMBs. Abstract : Traditional polymer electrolytes still have the disadvantages of not good thermal conductivity, poor thermal stability, and low porosity. Here we fabricate the composite polymer electrolyte membrane (CPEM) which have superior thermal stability (>360 °C), good mechanical strength, and wide electrochemical stability window (>5 V vs. Li + /Li). The all‐solid‐state lithium metal batteries assembled with the CPEM possess excellent rate capability.